2000
DOI: 10.1046/j.1365-2419.2000.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the spawning of cod (Gadus morhuaL.), sole (Solea soleaL.) and plaice (Pleuronectes platessaL.) in the Irish Sea as determined by generalized additive modelling

Abstract: Eleven ichthyoplankton cruises were undertaken covering most of the Irish Sea during the period February to June, 1995. To identify spawning localities and investigate temporal trends in egg production, the data on stage 1 A egg distributions of cod (Gadus morhua), plaice (Pleuronectes platessa) and sole (Solea solea) have been modelled using generalized additive models (GAMs). A two‐stage approach was adopted where presence/absence was firstly modelled as a binary process and a GAM surface subsequently fitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…Cruises were conducted in 2008 and 2009 on a well-described plaice spawning ground (Fox et al 2000a in the eastern Irish Sea (Fig. 1).…”
Section: Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cruises were conducted in 2008 and 2009 on a well-described plaice spawning ground (Fox et al 2000a in the eastern Irish Sea (Fig. 1).…”
Section: Field Samplingmentioning
confidence: 99%
“…Euphausiids have also been reported to consume fish eggs and larvae (Bailey et al 1993) but they were not abundant in the egg patch investigated. Euphausiids are much more common in the deeper parts of the western Irish Sea (Mauchline 1984) where they could be more important as predators of fish eggs, since these areas are also adjacent to fish spawning grounds (Fox et al 2000a).…”
Section: Use Of Molecular Probes In Marine Predation Studiesmentioning
confidence: 99%
“…Spawning has been extensively described and quantified for Irish Sea stocks of cod Gadus morhua, haddock Melanogrammus aeglefinus and plaice Pleuronectus platessa (Simpson 1959, Nichols et al 1993, Anonymous 1997, Ellis & Nash 1997, Fox et al 1997, 2000, Nash & Geffen 1999, Armstrong et al 2001. The accuracy of these estimates remains contentious, however, due to potential misidentification of eggs that are spawned simultaneously in spring in inshore coastal waters of the eastern and western Irish Sea (Anonymous 1997, Fox et al 2000, Armstrong et al 2001. Conventionally, marine fish eggs are identified by visual characteristics such as the presence, number and size of oil globules, size of the perivitelline space, yolk homogeneity and embryo pigmentation (Russell 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the relative abundance of these late-stage eggs or early-stage larvae is used to estimate the distribution and abundance of newly spawned (Stage IA) eggs (Page et al 1997, Bradbury et al 2000. Species that could be mistaken for the target species and are rare as larvae are often assumed to be absent from the plankton when in early developmental stages (Anonymous 1997, Fox et al 2000, Armstrong et al 2001. Later developmental stages are likely to have drifted from spawning grounds over time, introducing uncertainty to distribution estimates.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the water depth is a determinant factor in habitat use by small and large crayfish. Fox, Brien, Collas, and Nash (2000) modeled egg production patterns and egg density of three marine fish species in the Irish Sea using environmental variables. Location, depth, time, depthintegrated sea-temperature and salinity were incorporated into the presence/absence and egg production models.…”
Section: Introductionmentioning
confidence: 99%